Test sensitivity of a commercial serine protease digestion kit for the detection of Trichinella spiralis and Trichinella pseudospiralis larvae in pig muscle. (April 2019) - Franssen, F.; Johne, A.; van der Giessen, J.; Nöckler, K.; Mayer-Scholl, A.
Abstract: The reference method for Trichinella detection at meat inspection is the magnetic stirrer method (MSM) utilising HCl-pepsin for pooled sample digestion. Due to availability and quality issues with pepsin, alternative digestion methods are being offered, such as the Priocheck Trichinella AAD kit (T-AAD), based on serine endopeptidase digestion. In this study the T-AAD kit was compared to the reference method. Minced pork samples were spiked with T. spiralis muscle larvae (ML) with- and without capsule or T. pseudospiralis ML, and analysed with both tests. Test results of individually spiked test samples were analysed by generalised linear modelling. The T-AAD test kit was comparable to the reference method for the qualitative detection of T. spiralis in pigs, but not quantitatively. Overall, 94% of spiked T. spiralis were recovered using MSM against 75.2% when using T-AAD (p < 0.0001). Using the MSM 80.0% of spiked T. pseudospiralis were recovered against 20% with the T-AAD (p < 0.0001). Based on our experience with the T-AAD kit, we strongly recommend validating the method on site prior to introduction into routine diagnostic laboratories, but this will not alleviate the poor test sensitivity of the T-AAD for the detection of T. pseudospiralis . Highlights: Magnetic stirrer method (MSM) is the gold standard to detect Trichinella . T-AAD showed 4.6 times more false negatives than MSM for T. pseudospiralis . Accurate quantification of T. spiralis larvae was not possible using T-AAD.